Clinicopathological and molecular genomic features of monomorphic epitheliotropic intestinal T-cell lymphoma in the Chinese population: a study of 20 cases - Chunni Chen; Yuxi Gong; Yefan Yang; Qiuyuan Xia; Qiu Rao; Yang Shao; Liuqing Zhu; Junli Zhang; Xiao Li; Pan Ji; Boya Zhai; Xiang Zhang; et al. (BMC, 2021)
Abstract Background Monomorphic epitheliotropic T-cell lymphoma (MEITL) is an aggressive non-Hodgkin lymphoma with a high fatality rate. This study was aimed to explore the clinicopathological and molecular genetic features of MEITL in the Chinese population. Methods A retrospective analysis was performed based on the clinical manifestations and pathological features of 20 Chinese MEITL. 9 cases with paired diseased-normal tissues were also analyzed for molecular information by whole-exome sequencing. Results There were 14 men and 6 women with a median age of 58.5 (28-81) years. 17(17/20) lesions were located in the jejunum or ileum; 13(13/20) cases had ulcers or perforations. Microscopically, except for 1(1/20) case of pleomorphic cells, the monomorphic, middle-sized tumor cells infiltrating into the intestinal epithelial and peripheral intestinal mucosa recess could be seen in the other 19 cases. Immunohistochemistry showed that most of the tumor cells in MEITL were positive for CD3(20/20), CD8(17/20), CD43(19/20), and CD56(15/20), but negative for CD5(20/20). The most frequently mutated genes of these Chinese cases were STAT5B (4/9) and TP53 (4/9), not SETD2(2/9). JAK3 mutations (3/9) were also detected with a high mutated frequency. We demonstrated that mutations of JAK-STAT pathway-related genes and the amplification of Chromosome 9q appeared at the same time in most cases(5/9). Conclusions The clinicopathological features were consistent with that in previous western studies, but a special case with pleomorphic cells was found in this study. The co-occurrence of JAK-STAT pathway-related gene mutations and the amplification of Chr9q is a molecular feature of MEITL.